Assessment of Groundwater Vulnerability Using the DRASTIC Method: A Case Study of the Bued River Watershed (Journal of Asian Geography, 2026)
Groundwater plays a critical role in sustaining water supply for domestic, agricultural, and industrial uses, particularly in urbanising watersheds such as the Bued River Watershed in the Philippines. This study assessed the groundwater vulnerability of the watershed using the DRASTIC model integrated with Geographic Information System (GIS) mapping. The methodology involved evaluating seven hydrogeological parameters: depth to water table, net recharge, aquifer media, soil media, topography, impact of the vadose zone, and hydraulic conductivity. Data were obtained from relevant government agencies and processed using GIS to generate individual thematic layers and a composite vulnerability map. The findings indicate that approximately 90% of the watershed falls within a moderate vulnerability index, particularly in areas underlain by bedded sandstone, marine clastic formations, and karstic limestone lithologies, which are characterised by high permeability. In contrast, areas dominated by igneous and metamorphic rocks exhibited lower vulnerability due to their reduced porosity and permeability. The study concludes that the Bued River Watershed is moderately vulnerable to groundwater contamination, especially in its northern and central zones. It is recommended that local government units and water management agencies utilise the vulnerability map to inform land-use planning, groundwater protection strategies, and policy development. Future research should incorporate temporal assessments and additional hydrogeological data to improve the robustness and applicability of the findings.